Comparative Evaluation of Physical Fitness Components among Players of Selected Traditional Games of North-East India (International Journal of Food and Nutritional Sciences, 2023)
The present study aimed to compare selected physical fitness components among players of ten traditional games practiced across five North-Eastern states of India. A total of 450 male participants aged 14–18 years, representing ten traditional games, were selected through purposive sampling (n = 45 per game). Physical fitness was assessed using standardized field tests: 50 m dash (speed), 1000 m run (endurance), 4 × 10 m shuttle run (agility), standing broad jump (explosive strength), and sit and reach (flexibility). Descriptive statistics and one-way ANOVA were used to analyze inter-game differences. Results revealed no statistically significant differences (p > 0.05) among players of different traditional games in any of the physical fitness components. However, mean score variations indicated minor trends suggesting sport-specific influences on selected components. The findings suggest that traditional games, irrespective of type, contribute uniformly toward the holistic development of motor fitness.